Composite scaffolds of chitosan/polycaprolactone functionalized with protein of Mytilus californiensis for bone tissue regeneration - Olivas Armendariz, Imelda (2022)
Nowadays, the treatment for bone damage remains a significant challenge. As a result, the development of bioactive three-dimensional scaffolds for bone regeneration has become a key area of study within tissue engineering. This research is focused on the evaluation of the properties of Chitosan (Ch)/Polycaprolactone (PCL) scaffolds with the Mytilus californiensis protein by Thermally Induced Phase Separation (TIPS). This study used the extrapalleal fluid protein from Mytilus californiensis because it increases biological processes that support bone regeneration. Two methodologies were used for the scaffolds functionalization: (I) an immersion process in a solution with the protein and (II) the protein direct addition during the scaffold synthesis. The scaffolds were analyzed by Fourier Transformed Infrared Spectroscopy (FT-IR), Scanning Electron Microscopy (SEM), and Mechanical Compression test to determine the composition, morphology, and mechanical properties of each material. In vitro analysis of biodegradation, bioactivity, and biocompatibility were also performed. The scaffolds with the protein added directly presented superior properties in the tests of bioactivity and cellular proliferation, making these composites attractive for the area of bone regeneration.